Perilaku Permintaan Uang Islam: Antara Otentisitas dan Inovasi - Khoirul Umam (University of Darussalam Gontor, 2015)
In nowadays financial and monetary system, the crisis frequently occurs and becomes a part of its internal system. It indicates the fragility of financial and monetary conventional system and becomes the stimulant of a better system, namely Islamic financial and monetary system. The development of Islamic financial and monetary system demands a rapid innovation, but it should not go beyond the authenticity of Islamic system. Without innovation, the Islamic financial and monetary system will always be left behind, but without based on authenticity it will bring Islamic label on conventional system. This paper tries to discuss about the behavior of Islamic money demand, especially the state of velocity of money. The state of velocity of money is highly depended on to the ongoing money and financial concept. This paper shows that the preservation of authenticity in developing innovations in Islamic money and financial system will usher to the constant velocity of money. Otherwise, it can be concluded that the innovation of Islamic financial and money system without keeping authenticity of Islamic system can produce a different velocity state of money. Some empirical researches confirmed both results namely constant velocity so that monetary policy by targeting money supply can become effective, and there are some empiric researchers found a different result. Based on this, the development of innovations in Islamic financial and money system must be followed by the preservation of Islamic authenticity system. It demands the development of Islamic financial and money system theories which are free form any business motive intervention. Therefore, Islamic University is the most appropriate place to take the intellectual role by conducting researches and teaching the Islamic financial and monetary system.